Implementasi Metode Elimination Et ChoixTraduisant La Realite (ELECTRE) dalam Penentuan Pegawai Berprestasi - Delmayanti, Vera; Yunus, Yuhandri; Santony, Julius (Jurnal Informasi dan Teknologi, 2020)
The Kerinci Regency Cooperatives, Industry and Trade Office has a variety of employees whose competencies in their fields are for that purpose in improving an employee's performance by determining outstanding employees who aim to motivate and reward them for improving employee work performance. In determining this outstanding employee the data used are 3 samples of employee names as alternatives and some of the criteria on which decisions are made include Service Orientation, Integrity, Commitment, Discipline, and Cooperation. The results of the process of the ELECTRE method is to compare one employee with another employee and provide the results of priority value output in the form of assessment results or based on criteria that have been determined by the Office. The results of this process are recommended as outstanding employees at the Kerinci Regency Cooperatives, Industry and Trade Office.